FBXL3 serves as a suppressor of regenerative myogenesis - He, Wei; Han, Shiyuan; Wu, Yanming; Chen, Min; Xue, Ting; You, Hua; Chang, Ying; Liu, Song-Bai; Sun, Yi; Tang, Yinjiang; Shi, Xinghong; Han, Xingyu; et al. (Frontiers in Immunology, 2025)
Muscle regeneration hinges on the proliferation and differentiation of satellite cells. FBXL3, a member of the F-box protein family known for its role as a negative regulator of the circadian clock, is implicated in myogenesis. In this study, we demonstrate the expression of FBXL3 in satellite cells of adult mice, where it acts as a negative regulator of myogenic regeneration. This regulation occurs through the promotion of ubiquitination and degradation of TCF12, a transcription factor crucial for differentiation. Loss of FBXL3 activates MyoD and myogenin, thereby augmenting myogenic differentiation and regeneration. The role of FBXL3 in muscle regeneration was also confirmed using the tamoxifen-inducible Pax7-CreER recombination system. To unravel the regulatory mechanism of MyoD and myogenin by FBXL3, we conducted RNA sequencing on Fbxl3+/+and Fbxl3-/- primary myoblasts. Gene set enrichment analysis (GSEA) revealed that FBXL3 deficiency enriches the gene set associated with striated muscle cell development, including MEF2C, a regulator of myogenin expression. Through a search in the ChEA3 database, TCF12 emerged as the downstream candidate gene regulated by FBXL3 to modulate MEF2C. ChIP-PCR assays confirmed the enrichment of TCF12 on MEF2C promoter at three consensus sites. Dual-luciferase reporter assay validated that TCF12 activates the MEF2C promoter. This comprehensive study underscores the crucial role of FBXL3 in satellite cell-mediated myogenic regeneration and provides insights into the intricate regulatory network involving TCF12 and MEF2C.